Occupational Sex Segregation and its Consequences for the (Re-)Production of Gender Inequalities in the German Labour Market - Kleinert Corinna; Leuze Kathrin; Bächmann Ann-Christin; Gatermann Dörthe; Hägglund Anna Erika; Rompczyk Kai (Springer, 2025)
In Germany, the structuring principle connecting the educational system and the labour market is occupations. In theory, this occupational principle is gender-neutral, because both women and men are channelled into jobs according to the occupations for which they are trained. In practice, however, it means that patterns of occupational sex segregation in the education system are reproduced in the labour market. As a consequence, occupational sex segregation has important consequences for the subsequent employment biographies and life courses of women and men. In this chapter, we study the relevance of occupational sex segregation for the (re-)production of gender inequalities in the German labour market. More specifically, we examine long-term trends in occupational sex segregation, how occupational sex segregation is causally linked to other occupational characteristics, how these occupational characteristics translate into gender inequalities regarding non-monetary labour market outcomes, and how these occupational characteristics affect the gender wage gap
Education, Competence Development and Career Trajectories: analysing data of the national educational panel study (NEPS)